Estudo teórico e experimental da interação de elétrons com moléculas poliatômicas - Souza, Gabriel Luiz Cruz de (2010)
In this work, we present an improvement on theoretical study of electron scattering by medium-size molecules at intermediate incident energy range, lying from the ionization threshold to 1 keV. More specifically, the absorption effects which represent the influence of inelastic scattering channels on the elastic channel were accounted for via the Padé Approximant technique. Modifications were introduced in the EPolyScat-D computational code, developed originally by Lucchese and co-workers in order to include such effects. The modified code was applied to calculate differential (DCS), integral (ICS), momentum transfer (MTCS), total (TCS) and total absorption (TACS) cross for electron collision with mediumsize hydrocarbon molecules, namely, ethane (C2H6), propane (C3H8) and benzene (C6H6) in the low- and intermediate energies. Our theoretical results were compared with the experimental data measured in Laboratório de Espalhamento de Elétrons DQ UFSCar and with the existing theoretical and /or experimental data. The good agreement seen in such comparison shows the effectiveness of our method. The extension of the applicability of the present code in order to investigate also electron scattering by polar molecules is now underway. Additionally, an experimental part of the present work consists of the measurement of absolute DCS for electron scattering with sulphur dioxide molecule (SO2) in the 100 1000 eV energy range. Our DCS were compared with the existing theoretical and/or measured data reported by others research groups and showed good agreement.